Construção de uma sequência didática com situações-problema envolvendo matemática financeira - Gimenes, Deivid Geraldo (Universidade Federal de São Carlos, 2016)
This work deals with developing, structuring and implementation of a didactic sequence taught Financial Mathematics to high school students through reproduction environments able to provide them the opportunity to be protagonists in decisionmaking. Articulated with the French methodology of mathematics education known as Didactic Engineering, this pedagogical proposal has been designed with the aim of contributing to the youth actively participate in family financial planning. The first activity of the sequence focused on the inclusion of the student body in financial contexts in which situations were simulated conducive to learning and incorporating fundamental contents of Financial Mathematics. The second, favored the application of knowledge acquired, in scenarios where the Investment Analysis is essential for the provision of financial success. The results show that there was a significant learning capable of conferring the full potential students to apply the concepts covered in real situations, helping them to develop a new perspective on this important branch of mathematics.
Keywords: Matemática Financeira; Análise de Investimentos; Engenharia Didática; Planejamento Familiar; Mathematical Finance; Investment Analysis; Teaching Engineering; Family Planning; CIENCIAS EXATAS E DA TERRA